2010
DOI: 10.1259/bjr/52267127
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose evaluation in multidetector-row CT imaging for acute stroke with an anthropomorphic phantom

Abstract: ABSTRACT. This study evaluated radiation dose and dose reduction in CT imaging for acute stroke. Radiation doses in three types of CT imaging (i.e. non-contrast-enhanced CT, CT perfusion (CTP) and CT angiography (CTA)) were measured with an in-phantom dosimetry system for 4-, 16-and 64-detector CT scanners in 5 hospitals. To examine the relationship between image quality and radiation dose in CTA, image contrast-to-noise ratio was evaluated. Doses to the brain, lens, salivary glands and local skin obtained wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…Zhang et al 4 reported peak dose to eye lens and skin of 81 and 87 mGy, respectively, for the Philips Briliance 64 CT scanner at 80 kVp and 3750 mAs. Corresponding values found here for Philips Briliance iCT 256-slice CT scanner were 35% and 28% higher which may be attributed mainly to the double z-coverage allowed by the later scanner, i.e., 80 vs 40 mm, and secondarily to the 7% lower value of total mAs assumed in the study of Zhang et al 4 Compared to current results, Yamauchi-Kawara et al 8 and Cohnen et al 9 reported peak eye-lens doses lower by a factor of 10 which may be mainly attributed to the exclusion of the eye lenses from the primarily exposed head region. The range of the reported peak eyelens dose when eyes are primarily exposed is 81-279 mGy whereas the corresponding range when the eyes are not primarily exposed is 9.9-19.8 mGy.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Zhang et al 4 reported peak dose to eye lens and skin of 81 and 87 mGy, respectively, for the Philips Briliance 64 CT scanner at 80 kVp and 3750 mAs. Corresponding values found here for Philips Briliance iCT 256-slice CT scanner were 35% and 28% higher which may be attributed mainly to the double z-coverage allowed by the later scanner, i.e., 80 vs 40 mm, and secondarily to the 7% lower value of total mAs assumed in the study of Zhang et al 4 Compared to current results, Yamauchi-Kawara et al 8 and Cohnen et al 9 reported peak eye-lens doses lower by a factor of 10 which may be mainly attributed to the exclusion of the eye lenses from the primarily exposed head region. The range of the reported peak eyelens dose when eyes are primarily exposed is 81-279 mGy whereas the corresponding range when the eyes are not primarily exposed is 9.9-19.8 mGy.…”
Section: Discussioncontrasting
confidence: 55%
“…Therefore, reporting of peak tissue doses to skin, eye lens, brain parenchyma, and RBM may be far more important than an estimate of effective dose in brain perfusion CT studies. Despite, peak skin and peak eye-lens doses from brain perfusion CT studies have been reported in a few recent studies, 4,8,9 reported data on peak doses to brain and RBM are scanty. Besides, published dose data refer mostly to low-dose brain perfusion CT studies performed on MD CT systems with up to 64 detector rows.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, all patients who are examined with CTA are exposed to its risks, which include an approximate doubling of the radiation dose, contrast exposure, and incidental findings such as unruptured aneurysms, thyroid nodules, and lung nodules. 23 Emergent CTA protocols require injection of iodinated contrast without a laboratory assessment of renal function. Patients run a risk of developing contrast-induced nephropathy, especially if they have underlying chronic kidney disease (CKD).…”
Section: Should Ct Angiography Be a Routine Component Of Acute Strokementioning
confidence: 99%
“…14 To reduce radiation dose to patient during a DCE-CT scan, one can simply reduce tube voltage and tube current-exposure time product (mAs). [15][16][17] However, the associated image usually suffers from low signal to noise due to reduced current (mAs) and the radiation dose to patient could paradoxically increase if a study is repeated due to poor image quality. 17 In recent years, several studies reported the effectiveness of iterative reconstruction methods on low dose (low mAs) perfusion CT imaging for better image noise reduction, lowcontrast object detection, and, more importantly, quantitative perfusion values.…”
Section: Introductionmentioning
confidence: 99%